THE USE OF THINK PAIR SHARE LEARNING MODEL TO INCREASE CREATIVITY OF GRADE V STUDENTS - Fatimah, Siti; Santoso, Santoso; Riswari, Lovika Ardana (Indonesian Journal of Educational Development (IJED), 2024)
This research is motivated by monotonous learning using conventional models such as lectures can cause limited student creativity. The purpose of this study was to improve students' creativity in working on macrame skills by using the Think Pair Share model. Classroom Action Research method consisting of 2 cycles with 2 meetings. The research subjects in the fifth grade of SDN 1 Soco in the 2023/2024 school year were 18 students with 14 male students and 4 female students. The data analysis techniques used are quantitative and qualitative, qualitative data obtained from observations and interviews, while quantitative data through performance tests. The results showed significant results, the assessment of student creativity by applying the Think Pair Share learning model got an average score of 66 in cycle I with a percentage of completeness of 17%, increased to 88 in cycle II with a percentage of completeness of 89% which means it falls into the creative category.